An integrated method for measuring gas permeability and diffusivity of porous solids. (21st September 2020) - Manley, Shu San; Steindl, Patrick; Hewitt, Geoffrey F.; Bismarck, Alexander
Graphical abstract: Highlights: New apparatus enables concurrent determination of permeability and diffusivity. Large range of permeabilities, from nano Darcy to Darcy, can be measured. Tortuosities reliably accessible through transient diffusion experiments. Abstract: An integrated gaseous transport apparatus was designed not only to measure permeability (by the pressure rise technique) but also to study both steady state and (importantly) transient diffusion of oxygen in nitrogen in the pores of a porous material. The apparatus allows for the characterisation of porous media with a wide range of permeabilities and yielded accurate values of the viscous permeability and the slip flow coefficient. Experiments were also carried out in the non-Darcy flow regime. The diffusion measurements provide information on the ratio of the diffusion coefficient in the media to that in free space; this ratio is also a specific property of porous media. Combining the steady state and transient diffusion measurements, it was possible to deduce the effective porosity and the pore length. Berea sandstones with a range of porosities were analysed using both techniques and the results of the measurements are presented.